Design of Information Systems Web-Based Inventory Using The FAST (The Framework Of Application System Thinking) Method at PT.Whoto Indonesia Sejahtera in Bandung - Rosalin Samihardjo; Iqbal Azhim Hidayat (Association for Scientific Computing Electrical and Engineering, 2020)
The application of information system technology is now essential for companies to run a fast, accurate, reliable, and detailed information flow. PT. Whoto Indonesia Sejahtera Bandung branch is a company engaged in the marketing and distribution of skincare products. Inventory information system in PT. Whoto Indonesia Sejahtera Bandung has not been fully computerized and still uses Microsoft Excel, starting from recording incoming goods, requesting goods from the sales department, processing goods out by the warehouse to making reports, so there will be a possibility when an error occurs in the process search for data needed. The best solution to solve existing problems is to design a web-based inventory application because it is better than recording the previous system so that it can find out and make it easier to provide fast, accurate, and accurate information. Website-based inventory information system design uses a system development method that is FAST (Framework for Application System Thinking) consisting of phases of Scope Definition, Problem Analysis, Requirements Analysis, Logical Design, and Physical Design. The programming languages used in the design of this information system are HTML and PHP and MYSQL as the database.